SARS-CoV-2 Nucleocapsid Protein Has DNA-Melting and Strand-Annealing Activities With Different Properties From SARS-CoV-2 Nsp13 - Zhang, Bo; Xie, Yan; Lan, Zhaoling; Li, Dayu; Tian, Junjie; Zhang, Qintao; Tian, Hongji; Yang, Jiali; Zhou, Xinnan; Qiu, Shuyi; Lu, Keyu; Liu, Yang (Frontiers in Microbiology, 2022)
Since December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread throughout the world and has had a devastating impact on the health and economy. The biochemical characterization of SARS-CoV-2 proteins is important for drug design and development. In this study, we discovered that the SARS-CoV-2 nucleocapsid protein can melt double-stranded DNA (dsDNA) in the 5'-3' direction, similar to SARS-CoV-2 nonstructural protein 13. However, this unwinding activity was more than 22 times weaker than that of SARS-CoV-2 nonstructural protein 13 and the melting process was independent of nucleoside triphosphates and Mg2+. Interestingly, at low concentrations, the SARS-CoV-2 nucleocapsid protein exhibited stronger annealing activity than SARS-CoV-2 nonstructural protein 13; however, at high concentrations, it promoted the melting of dsDNA. These findings have deepened our understanding of the SARS-CoV-2 nucleocapsid protein and provide novel insights for antiviral drug development.